1992
DOI: 10.1007/bf00145322
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiologic study of environmental and genetic factors in congenital hydrocephalus

Abstract: Risk factors were studied in 96 children with congenital hydrocephalus (CH) coming from 118,265 consecutive births of known outcome. Hydrocephalus with neural tube defects, intracranial tumors or secondary to brain atrophy were excluded. The prevalence of CH was 0.81 per thousand. Diagnosis was performed prenatally in 41 cases. Forty-three (44.8%) of the cases had hydrocephalus without other malformations (isolated hydrocephalus), 18 (18.7%) infants had recognized chromosomal or non-chromosomal syndromes and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
2
7

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 14 publications
4
29
2
7
Order By: Relevance
“…The differences between them however make them hard to compare: children with spina bifida were included or not, fetal deaths were taken into consideration or not, studies were population based or hospital based, and there were possible ethnic differences. In the studies since the 1980s, it is agreed that the incidence of congenital and infantile hydrocephalus (20 weeks gestational age-1 year) is 0.12 2.5 per 1000 live and stillbirths [22,46,61,63]. In a group of Swedish children with prenatal onset hydrocephalus [22], toxoplasmosis was an important causative factor; in the peri/postnatal group haemorrhage was the main determinant in preterm babies.…”
Section: Incidence and Frequent Causesmentioning
confidence: 95%
“…The differences between them however make them hard to compare: children with spina bifida were included or not, fetal deaths were taken into consideration or not, studies were population based or hospital based, and there were possible ethnic differences. In the studies since the 1980s, it is agreed that the incidence of congenital and infantile hydrocephalus (20 weeks gestational age-1 year) is 0.12 2.5 per 1000 live and stillbirths [22,46,61,63]. In a group of Swedish children with prenatal onset hydrocephalus [22], toxoplasmosis was an important causative factor; in the peri/postnatal group haemorrhage was the main determinant in preterm babies.…”
Section: Incidence and Frequent Causesmentioning
confidence: 95%
“…Stoll et al [17]in their evaluation of 96 children with congenital hydrocephalus, which excluded cases of prenatal and perinatal infections and hemorrhage, reported a consanguinity rate of 6.6%. This was 6 times the frequency in their controls.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this high rate of consanguinity among parents of children with hydrocephalus, only one sibling of a case had hydrocephalus. Stoll et al [17]concluded that parents of children with hydrocephalus are significantly more often related to each other than parents of controls. Varadi et al [18], suggested that couples who had one previous child with hydrocephalus, have a 4% incidence of hydrocephalus in a sibling.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of congenital hydrocephalus internus (CHI) varies between 0.5 and 2.5 per 1000 newborns for dierent populations [4,11,13,22,25]. Retrospective studies report a low overall recurrence risk (0.6±1.4%) of CHI [4,7].…”
Section: Introductionmentioning
confidence: 96%